Efektivitas Bantuan Program Indonesia Pintar (PIP) Terhadap Motivasi di MTs Putri Siti Hajar - Safitri, Nita Andriani; Nurlatifah, Nurlatifah; Hakim, Ripki Lukmanul; Hidayat, Ara (IAIN Syekh Nurjati Cirebon, 2021)
The percentage of poor people in Indonesia has increased by 0.41% which is a challenge for the government so that the hope of education is not cut off. Education fee assistance is expected to help allocate education costs, either directly or indirectly, which will have an impact on the motivation of students. So that the purpose of this study is to analyze the effectiveness of PIP assistance on the motivation of students at MTs Putri Siti Hajar Bandung. The method used in this research is the quantitative method. Collecting data by means of interviews and questionnaires with a total sample of 23 respondents. The results showed that the PIP assistance activity was 61.3%, while the motivation of students at MTs Putri Siti Hajar Bandung was equal to. The effectiveness of PIP assistance has a positive and significant effect on the motivation of students at MTs Putri Siti Hajar Bandung by 16.2%.Presentase penduduk miskin di Indonesia naik sebesar 0,41 % menjadi tantangan bagi pemerintah agar harapan pendidikan tidak terputus. Bantuan biaya pendidikan diharapkan dapat membantu pengalokasian biaya pendidikan baik secara langsung maupun tak langsung yang memberi dampak pada motivasi peserta didik. Sehingga tujuan penelitian ini yaitu menganalisis efektifitas bantuan PIP terhadap motivasi peserta didik di MTs Putri Siti Hajar Bandung. Metode yang digunakan dalam penelitian ini ialah metode kuantitatif. Pengumpulan data dengan cara wawancara dan kuisioner dengan jumlah sampel sebanyak 23 responden. Hasil penelitian menunjukan bahwa ewktifitas bantuan PIP sebesar 61,3 %, sedangkan motivasi peserta didik di MTs Putri Siti Hajar Bandung sebesar . Efektifitas bantuin PIP berpengaruh secara positif dan signifikan terhadap motivasi peserta didik di MTs Putri Siti Hajar Bandung sebesar 16.2 %.Keywords: Effectiveness, Cost of Education, Motivation